Barn owl diet and prey fluctuations in the Jura mountains, eastern France - Michelat Dominique; Giraudoux Patrick (Zenodo, 2022)
Based on pellet collection, the diet of the Barn Owl ( Tyto alba ) was studied over a 8-year period in the Jura mountains, eastern France, during two population surges of its main prey (common vole, Microtus arvalis and montane water vole, Arvicola amphibius ); Small mammals were sampled by trapping and index methods. Results have been published in the Canadian Journal of Zoology ( Bernard et al. 2010 ). Dominique Michelat collected Barn Owl pellets and identified prey items, Pierre Delattre, Jean-Pierre Quéré Jean-Pierre Damange and Patrick Giraudoux sampled small mammals. Patrick Giraudoux managed the data. Small_mammals_trapping.txt is the file of the raw trapping results for small mammals (instant abundance index i t in the article) diet_smm.txt is a file with: the small mammal density computed by season (d t in the article, rough estimate of densities in number of individuals per ha for Apodemus spp. , Myodes glareolus , Microtus arvalis , or weighted interpolated i t for the other species) the ratios of each category of prey items on the total number of items collected in the church tower of three sites, Levier , Chapelle d'Huin and Le Souillot . For details see the material and methods of the article. FILE DESCRIPTION diet_smm.txt date, year and season: year on two digits, then P, E, A, H respectively for Printemps (Spring), Été (Summer), Automne (Autumn), Hiver (Winter) at_t, abundance index of Arvicola amphibius (ex A. terrestris ) ap_t, rough density estimate of Apodemus sp. cg_t, rough density estimate of Myodes glareolus ma_t, rough density estimate of Microtus arvalis sa_t, relative abundance of Sorex spp. n_l, number of prey items at Levier ma_p_l, ratio of M. arvalis prey items at Levier at_p_l, ratio of A. amphibius prey items at Levier apcg_p_l, ratio of Apodemus spp. or Myodes glareolus prey items at Levier sa_p_l, ratio of Sorex spp. prey items at Levier au_p_l, ratio of other prey items at Levier n_ch, number of prey items at Chapelle d'Huin map_ch, ratio of M. arvalis prey items at Chapelle ...